Freqüência e etiologia das dermatomicoses em pacientes atendidos no Hospital Giselda Trigueiro, Natal, RN - Calado, Nicácia Barbosa (2005)
Dermatomycoses are fungal infections that attack the skin, hair and nails, in addition to the mucosal and cutaneous-mucosal zones. Objective: Observe the frequency of dermatomycoses, identify etiological agents and establish an association between the results and sex. Age, collection site, time and lesion location. Methods: Between February, 2002 and December, 2004, samples were collected from patients at Giselda Trigueiro Hospital in Natal, Brazil, by lesion scraping and hair removal, following 70% alcohol disinfection, and submitted to direct and culture examination. Results: Of the 817 lesions collected, 325 (39.8%) were fungus positive, with the hair collection site yielding the highest number of positive results (65.8%) and the scalp and hair representing the most frequent lesion sites (65.9%). Negative results occurred mainly in the lower limbs (78.6%). Of the species identified, 55.9% were yeasts, 41.6% dermatophytes and 2.5% Fusarium spp. Non-albicans Candida was the most isolated yeast (43.3%), mainly in females (61.7%) over the age of 40 years (56.4%). T. rubrum was the most isolated dermatophyte (67.9%),notably in males (59.2%) in the 0-20 age group (44.7%). With respect to collection site, 73.9% of the dermatophytes were present in the skin and 61.1% of the yeasts in the nails. When assessing the collection site, the inguinocrural regional was 22.6% positive for dermatophytes, and the nails and hands, 41.8% for yeasts. Conclusions: The results obtained verified that: most of the positive lesions were found in the hair, whereas skin and nail lesions yielded more negative results; T. rubrum was the most isolated dermatophyte and non-albicans candida the most commonly found yeast; positivity was greater in males in the 0-20 year age group at the skin site and in the inguinocrural region, while yeasts were more frequent in females in the over-40 age group at the nail sites